Analysis Of Relationship Between The Sea Tidal And The Formed Sedimentation(Case Study;Pier Container Port Surabaya) - Lailatul Qhomariyah (Jurnal Teknik ITS, 2016)
Indonesian archipelago has a high necessity of sea transportation to support the trade activities and mobility between one island and another. The harbor security is an important factor to ensure the safety of the ships which are being leant there, therefore the sedimentation is needed to be observed in order to find out the changes of sedimentation so that the ship would not run aground. The formation of sedimentation in the dock is influenced by several factors, one of them is tidal. Domestic dock container port of Surabaya is one the docks that facilitates dock ships at the jetty port in East Java. To observe the influence of the tides to the dock sedimentation, it is necessary to know the changes of sedimentation, so the security of the ships that will be dock could be guaranteed.The results of this study was finding the impacts of tidal phenomena to the sediment formed in the domestic dock container port Surabaya we can conclude that when the Formzahl number is greater than the previous year, the sedimentation volume will also increase. The sedimentation volume in 2011 amounted to 9.460 m3 with Formzahl numbers of 0,662 is used as the reference to a sedimentation volume increasing in 2012 amounted to 49.537 m3 with formzahl number of 0,819. The increasing formzahl numbers which also means increase in the phenomenon of ebb and flow of sea water, has shown a difference of sedimentation volume from 2011 to 2012 amounted to 40.077 m3. And In the sedimentation volume in 2013 amounted to 14.306 m3 with a formzahl number of 0,722 is used as the reference to an increase in sedimentation volume in 2014 amounted to 35.102 m3 with formzahl number of 0,758. The increasing formzahl numbers which also means an increase in the phenomenon of ebb and flow of sea water which has resulted in a difference of sedimentation volume from 2013 to 2014 amounted to 20 ANALYSIS OF RELATIONSHIP BETWEEN THE SEA TIDAL AND THE FORMED SEDIMENTATION (CASE STUDY : PIER CONTAINER PORT , SURABAYA)